Physical Chemistry from a Different Angle - Job, Georg; Ru¨ffler, Regina (Springer, 2016)
Experience has shown that two fundamental thermodynamic quantities are especially difficult to grasp: entropy and chemical potential—entropy S as quantity associated with temperature T and chemical potential μ as quantity associated with the amount of substance n. The pair S and T is responsible for all kinds of heat effects, whereas the pair μ and n controls all the processes involving substances such as chemical reactions, phase transitions, or spreading in space. It turns out that S and μ are compatible with a layperson’s conception. In this book, a simpler approach to these central quantities—in addition to energy—is proposed for the first-year students. The quantities are characterized by their typical and easily observable properties, i.e., by creating a kind of “wanted poster” for them. This phenomenological description is supported by a direct measuring procedure, a method which has been common practice for the quantification of basic concepts such as length, time, or mass for a long time. The proposed approach leads directly to practical results such as the prediction— based upon the chemical potential—of whether or not a reaction runs spontaneously. Moreover, the chemical potential is key in dealing with physicochemical problems. Based upon this central concept, it is possible to explore many other fields. The dependence of the chemical potential upon temperature, pressure, and concentration is the “gateway” to the deduction of the mass action law, the calculation of equilibrium constants, solubilities, and many other data, the construction of phase diagrams, and so on. It is simple to expand the concept to colligative phenomena, diffusion processes, surface effects, electrochemical processes, etc. Furthermore, the same tools allow us to solve problems even at the atomic and molecular level, which are usually treated by quantum statistical methods. This approach allows us to eliminate many thermodynamic quantities that are traditionally used such as enthalpy H, Gibbs energy G, activity a, etc. The usage of these quantities is not excluded but superfluous in most cases. An optimized calculus results in short calculations, which are intuitively predictable and can be easily verified.
Introducing Chemical Equilibrium, Kinetics and Electrochemistry by Numerous Experiments